2016
DOI: 10.1093/hsw/hlw061
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Not Following Up with Recommended Testing in the Diagnosis of Newborn Hearing Loss

Abstract: Children's hearing is a public health concern, and universal newborn hearing screenings are the first step in detecting and treating congenital hearing loss. Despite the high rate of participation in such programs, loss to follow-up (LTF) with additional recommended diagnosis and treatment has been a persistent problem. The current research seeks to expand the knowledge base at the point of diagnosis, where there is a large drop-off in parents following through with recommended care. This research was organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
0
19
1
2
Order By: Relevance
“…The results from the SEM indicate that both maternal depression and believing that hearing loss can have serious consequences for their child’s life significantly predicted LTF at rescreening, with social support moderating maternal depression, and effect sizes indicate that these differences may have important practical significance. These results are not consistent with previous research that examined biopsychosocial factors related to LTF at the point of diagnosis, which indicated that LTF was most associated with parents’ race/ethnicity and access to health-care professionals (Zeitlin et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results from the SEM indicate that both maternal depression and believing that hearing loss can have serious consequences for their child’s life significantly predicted LTF at rescreening, with social support moderating maternal depression, and effect sizes indicate that these differences may have important practical significance. These results are not consistent with previous research that examined biopsychosocial factors related to LTF at the point of diagnosis, which indicated that LTF was most associated with parents’ race/ethnicity and access to health-care professionals (Zeitlin et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…A prospective study identifying predictors of LTF at diagnosis included race/ethnicity and access to health-care professionals (Zeitlin, Auerbach, Mason, Spivak, & Reiter, 2017). In that study, parents who identified as African American were less likely to return for diagnostic testing than individuals of all other racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…17 Regarding follow-up after failed newborn hearing screening, there is also evidence in urban areas that African American babies are at a significant higher risk of being lost to follow-up and have limitations in access to care. 23 …”
Section: Delays In Pediatric Hearing Healthcare Deliverymentioning
confidence: 99%
“…Embora estatisticamente as crianças que realizaram a TAN tenham concluído mais precocemente o diagnóstico de PA do que as que não a realizaram, As dificuldades de ingresso no atendimento especializado foram relatadas por 30% dos pais/ responsáveis, sendo que o acesso a profissionais de saúde é fator relevante para a adesão das famílias aos procedimentos de diagnóstico e intervenção audiológica, após falha na TAN: quanto maior o acesso, maior a adesão 28 .…”
Section: Discussionunclassified